PROFIL USAHA PEMBUATAN TEMPE CV CIPTA PANCA PERSADA KLEAK KECAMATAN MALALAYANG KOTA MANADO - Silva ., Tangkabiringan; Benny Adrian Berthy Sagay; Melsje Yellie Memah (Sam Ratulangi University, 2019)
This study aims to examine the profile of tempe making business at CV Cipta Panca Persada. The business profile is limited to obtaine of the amount of profits. This research was conducted for 3 monthsstarting from May to July 2018. The data used in this study are primary data and secondary data. Primary data is obtained from direct interviews with business owners (one respodent) using a list of questions that have been provided. While secondary data is obtained from the Agriculture Faculty library, the internet by using a google search engine to access articles from various scientific journals and theses from other universities related to this research topic concerning business profile. The results showed that the amount of tempe produced in one day was 50 packs of small packs at a price of Rp. 3,500 per package and 200 medium packages at Rp. 6,500 per package. The production process is one month (31 days) in July 2018, obtaining a total revenue of Rp. 39,000,000 with a total cost of Rp. 16,775,714,resulting in a profit of Rp. 22,224,286. -*eprm*